Motyw podróży jako element narracji tanecznej – próba rekonesansu zjawiska w świetle wybranych tematów spektakli baletowych XVIII wieku - Reglińska-Jemioł, Anna (Colloquia Litteraria, 2023)
The art of ballet in the Enlightenment era was a perfect tool of socio-cultural communication. It has fulfilled the curiosity of knowledge of “new worlds”, also referring to images preserved in the audience’s memory thanks to earlier readings (the popular topic was the theme of Telemachus’ voyage). Moreover, introducing exotic elements, foreshadowed the upcoming changes in the form of stage presentation. The literary record of ballet landscapes, remained on the pages of the librettos, exists as an important source for research into the history of theater, as well as a testimony to the culture and aesthetics of the age of lights.